Revising the Principle of Alternate Possibilities - Siegel, Max (Stance: an international undergraduate philosophy journal, 2013)
This paper examines the position in moral philosophy that Harry Frankfurt calls the Principle of Alternate Possibilities (PAP). The paper first describes the principle as articulated by A.J. Ayer. Subsequently, the paper examines Frankfurt’s critique and proposed revision of the principle and argues that Frankfurt’s proposal relies on an excessively simplistic account of practical reasoning, which fails to account for the possibility of moral dilemmas. In response, the paper offers a further revision of PAP, which accounts for Frankfurt’s critique, moral dilemmas, and the challenge of causal determinism.